2018
DOI: 10.1080/20473869.2018.1446704
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of mothers’ experiences of supporting the sexual development of their sons with autism and an accompanying intellectual disability

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 25 publications
5
37
0
5
Order By: Relevance
“…Moreover, their children had not engaged in any improper sexual behavior, and their lives were under parental supervision. Numerous mothers expressed worry that SE might heighten sexual desire or activity, which could lead to inappropriate sexual behavior, similar to previous studies [19,33]. In contrast, many reviews of the literature have stated that SE may assist in the sexual development and sexual demand of children and young PWD, as well as contribute to their health and well-being [2,34].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, their children had not engaged in any improper sexual behavior, and their lives were under parental supervision. Numerous mothers expressed worry that SE might heighten sexual desire or activity, which could lead to inappropriate sexual behavior, similar to previous studies [19,33]. In contrast, many reviews of the literature have stated that SE may assist in the sexual development and sexual demand of children and young PWD, as well as contribute to their health and well-being [2,34].…”
Section: Discussionsupporting
confidence: 69%
“…Previous research has emphasized the difficulties parents experience when discussing sexual topics with their children with IDs due to a paucity of knowledge and training in SE, as well as children's difficulty grasping the topic [17,18]. A previous review also showed that parental hurdles to delivering SE to their children with IDs are significantly influenced by family, religious, and sociocultural aspects [7,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study by Pryde & Jahoda (2018) has revealed that mothers of male children with intellectual disabilities in adolescence and young adulthood recognise that their son's sexual development is important; however, they remain apprehensive in providing sex education in fear that it would only increase their sons' sexual interest. It is possible that children's sexual development during adolescence negatively affects the mental health of their mothers, becoming one of the biggest stressors.…”
Section: Discussionmentioning
confidence: 99%
“…4,[10][11][12]20,21 The absence of sexual education programs for adolescents with ASD makes parents the primary agent in meeting the sexual development needs of ASD adolescents, amid limited information and support felt by parents, lack of experience in providing sexual education to ASD adolescents, low levels of parental confidence, confusion about when and the right way to start providing sexual education, as well as concerns about the appropriateness of sexual education provided. 1,4,[22][23][24][25][26] This study aims to explore the experience of parents in providing sexual education to children or adolescents with ASD.…”
Section: Introductionmentioning
confidence: 99%